Respectful Maternity Care: Concept Paper - Tsomondo, Ethel; Chihava, Itai; Kasu, Christine Mary; Mugadza, Gladys (IJRDO -JOURNAL OF HEALTH SCIENCES AND NURSING, 2017)
There are varying perceptions regarding the meaning of respectful maternity care (RMC) amongservice providers and the women cared for despite being an area of concern for decades.ObjectiveThe objective of the concept paper was to determine what respectful maternity care means for thepurpose of measuring it.MethodologyWalker and Avant (2011) concept analysis model was used to guide this paper.The following search engines, Google Scholar, Pubmed and Medline were utilised to select 15articles relevant to the concept of interest.Results:The meaning of RMC is not very clear to both clients and care givers, policies are not beingtranslated to action fully for effective RMCConclusionThe curricula of care providers’ education to emphasise on affective domain skills and furtherresearch and action on findings to improve RMC.